Pharmacokinetics of Mephedrone Enantiomers in Whole Blood after a Controlled Intranasal Administration to Healthy Human Volunteers - Joanna Czerwinska; Mark C. Parkin; Agostino Cilibrizzi; Claire George; Andrew T. Kicman; Paul I. Dargan; Vincenzo Abbate (MDPI AG, 2020)
Mephedrone, which is one of the most popular synthetic cathinones, has one chiral centre and thus exists as two enantiomers: R-(+)-mephedrone and S-(−)-mephedrone. There are some preliminary data suggesting that the enantiomers of mephedrone may display enantioselective pharmacokinetics and exhibit different neurological effects. In this study, enantiomers of mephedrone were resolved via chromatographic chiral recognition and the absolute configuration was unambiguously determined by a combination of elution order and chiroptical analysis (i.e., circular dichroism). A chiral liquid chromatography tandem mass spectrometry method was fully validated and was applied to the analysis of whole blood samples collected from a controlled intranasal administration of racemic mephedrone hydrochloride to healthy male volunteers. Both enantiomers showed similar kinetics, however, R-(+)-mephedrone had a greater mean Cmax of 48.5 ± 11.9 ng/mL and a longer mean half-life of 1.92 ± 0.27 h compared with 44.6 ± 11.8 ng/mL and 1.63 ± 0.23 h for S-(−)-mephedrone, respectively. Moreover, R-(+)-mephedrone had a lower mean clearance and roughly 1.3 times greater mean area under the curve than S-(−)-mephedrone. Significant changes in the enantiomeric ratio over time were observed, which suggest that the analytes exhibit enantioselective pharmacokinetics. Even though the clinical significance of this finding is not yet fully understood, the study confirms that the chiral nature, and consequently the enantiomeric purity of mephedrone, can be a crucial consideration when interpreting toxicological results.